VASCULAR PLANTS OF MANGROVE FOREST IN ARGAO, CEBU, PHILIPPINES - Lillo, Edgardo P; Alcazar, Steve Michael T; Nuevo, Ritchie U; Malaki, Archiebald Baltazar B (Journal of Agriculture and Technology Management; Tropical Technology Journal Volume 18 No. 1, 2015, 2015)
The primary aim of the study was to assess the species composition of vascular plants in mangrove forest of Argao, Cebu, Philippines. A 20m x 20m quadrat was established within the transect line at 250m intervals. A total of 11 plots were established in the site. All the plant species within the quadrat was identified and recorded. The study identified 22 species of vascular plants in mangrove forest of Argao, under 11families and 14 genera. The mangrove forest of Argao was dominated by the species of Rhizophora stylosa Griff, Ceriops decandra Ding Hou, and Lumnitzera racemosa Willd. The most abundant family was Rhizophoraceae with 8 species followed by 3 species of Avicenniaceae. While the family of Combretaceae, Myrsinaceae, and Sonneratiaceae had two species each and Bombacaceae, Meliaceae, Myrtaceae, Euphorbiaceae, and Arecaceae had one species. It was also found out that some of the mangrove species in the site has medicinal and commercial values derived from their resin. The fruits of busain (Bruguiera gymnorrhiza) were used as substitute medicine for sore eyes and pedada (Sonneratia caseolaris) for hemorrhage control. The mangrove forest of Argao needs to be protected and conserved because of its diversity, medicinal value. This forest is representing the remaining intact mangrove forest in the southern part of Cebu province.